Mass drug administration for trachoma elimination in a pastoral conflict area in Baringo County, Kenya: A study on barriers to coverage and compliance. - Bridget W Kimani; Tabitha W Kanyui; Paul M Gichuki; Collins O Okoyo; Titus K Watitu; Wyckliff P Omondi; Doris W Njomo (PLoS Neglected Tropical Diseases)
Trachoma, a neglected tropical disease (NTD), is the leading infectious cause of blindness worldwide. It is caused by repeated ocular infections with the bacteria Chlamydia trachomatis. Treatment coverage achieved in Baringo County, Kenya in 2020 and 2021 was 80% and 79% respectively, further investigation at the lower levels known as wards shows coverages ranging between 48% to 57% which are far below the WHO recommended threshold of at least 80% of the target population should be reached with MDA The objective of this study was to identify barriers of community participation and access to mass drug administration for trachoma elimination in a pastoral conflict area of Baringo County, Kenya. Sixteen focus group discussions were conducted with community members and four among community health volunteers. Eight county and sub-county leaders and fourteen opinion leaders participated in in-depth interviews. Patients with trichiasis took part in six micro-narrative surveys. All study participants were purposively selected and the number of FGDs, interviews, and micro-narrative surveys were determined by the saturation model, an iterative design was employed for data collection and analysis and further sample selection to give early insights and influence the selection of more participants. Although community members were aware of trachoma and the benefits of MDA, poor knowledge of trachoma etiology exists, with misconceptions attributing it to dirt, dust, flies, and even witchcraft. Women, children, and elderly persons were perceived to be at a higher risk of infection. The remoteness of some villages and towns hindered awareness creation resulting in some community members being unaware of trachoma and MDA. Side effects like diarrhea, nausea, headache, and drowsiness discourage participation. Drug size and taste are perceived as negative factors. Lack of information on side effects and their management contributes to hesitancy. Considering the perspectives of nomadic people and understanding context-specific risks, supporting the design of community-led interventions is critical in the development of effective MDA strategies, which can aid in halting trachoma transmission.